PERAN DOSEN DALAM MEMBANGUN KESADARAN MULTIKULTURAL MAHASISWA DI PROVINSI JAMBI: TINJAUAN MANAJEMEN PENDIDIKAN DAN TATA KELOLA INSTITUSI - Andini Fitri; Tiara Andrinie; Eva Iryani (CV Widina Media Utama, 2026)
This research is motivated by the increasing student heterogeneity in Jambi Province across 55 public and private universities, including the presence of international students, yet not balanced by systemic lecturer readiness to manage cultural diversity. The purpose of this study is to analyze the role of lecturers in building students' multicultural awareness and to identify institutional governance barriers hindering its optimization. This research employs a qualitative approach using library research. The findings identify four typologies of lecturer roles: inclusive learning facilitators, ethical role models, intercultural bridges, and agents of campus cultural transformation. The optimization of these roles is hindered by the unequal distribution of lecturers' cultural competence, the dominance of mono-cultural pedagogical approaches in private universities, and the absence of systematic institutional policies. The contribution of this study is to extend the multicultural education management model across three simultaneous intervention levels: individual, pedagogical, and institutional. The novelty of this study lies in identifying the structural gap between public and private universities in Jambi Province as a determining factor for successful multiculturalism management. This study concludes that simultaneous interventions at these three levels are required to create an inclusive and culturally just campus ecosystem. ABSTRAKPenelitian ini dilatarbelakangi oleh meningkatnya heterogenitas mahasiswa di Provinsi Jambi yang tersebar di 55 perguruan tinggi negeri dan swasta, termasuk kehadiran mahasiswa internasional, namun belum diimbangi dengan kesiapan sistemik dosen dalam mengelola keragaman budaya. Tujuan penelitian ini adalah menganalisis peran dosen dalam membangun kesadaran multikultural mahasiswa serta mengidentifikasi hambatan tata kelola institusional yang menghambat optimalisasinya. Penelitian menggunakan pendekatan kualitatif dengan studi kepustakaan. Hasil penelitian mengidentifikasi empat tipologi peran dosen: fasilitator pembelajaran inklusif, teladan etis, jembatan antarbudaya, dan agen transformasi budaya kampus. Optimalisasi peran tersebut terhambat oleh ketimpangan kompetensi kultural dosen, dominasi pedagogis mono-kultural di perguruan tinggi swasta, serta absennya kebijakan institusional sistematis. Kontribusi penelitian ini adalah memperluas model peran dosen dalam pendidikan multikultural dari perspektif manajemen pendidikan pada tiga level intervensi simultan: individu, pedagogis, dan institusional. Kebaruan penelitian ini terletak pada identifikasi kesenjangan struktural antara PTN dan PTS di Provinsi Jambi sebagai faktor determinan keberhasilan pengelolaan multikulturalisme. Penelitian ini menyimpulkan perlunya intervensi simultan pada ketiga level tersebut untuk menciptakan ekosistem kampus yang inklusif dan berkeadilan budaya.